Splitting of cell clusters and bifurcation of bryozoan branches - Goldwasser, L; Maini, P; Murray, J (1989)
We present a cell mechanical model that exhibits the pattern-forming behaviour of a cluster of cells at the growing tips of bryozoan branches. The crucial event in the production of the overall branching pattern is the splitting of the cluster into two clusters, rather than the formation of the cluster from a uniform distribution. In simulations, the uniform cell distribution initially evolved, as indicated by a linear analysis, either to a spatially patterned state, or to a temporally oscillating state. We suggest that the same processes responsible for the formation and behaviour of the cell cluster may also be responsible for tip branching.